1995
DOI: 10.1021/bi00046a033
|View full text |Cite
|
Sign up to set email alerts
|

Role of the PufX protein in photosynthetic growth of Rhodobacter sphaeroides. 2. PufX is required for efficient ubiquinone/ubiquinol exchange between the reaction center QB site and the cytochrome bc1 complex.

Abstract: The PufX membrane protein is essential for photosynthetic growth of Rhodobacter sphaeroides because it is required for multiple-turnover electron transfer under anaerobic conditions [see accompanying article; Barz, W. P., Francia, F., Venturoli, G., Melandri, B. A., Verméglio, A., & Oesterhelt, D. (1995) Biochemistry 34, 15235-15247]. In order to understand the molecular role of PufX, light-induced absorption spectroscopy was performed using a pufX- mutant, a pufX+ strain, and two suppressor mutants. We show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
97
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(108 citation statements)
references
References 32 publications
10
97
1
Order By: Relevance
“…We thus again observed a "significant but moderate" effect of the PufX deletion. Similar experiments were reported by Barz et al (18) and Francia et al (15), who found a larger slowing (Ͼ10-fold) and a pronounced lag of ϳ9 ms before the onset of the reduction kinetics. In our experiments, the time course of heme b reduction is sigmoidal, with a lag of only ϳ2 ms. We do not know the origin of this discrepancy.…”
Section: Functional Study Of Pufxsupporting
confidence: 90%
See 3 more Smart Citations
“…We thus again observed a "significant but moderate" effect of the PufX deletion. Similar experiments were reported by Barz et al (18) and Francia et al (15), who found a larger slowing (Ͼ10-fold) and a pronounced lag of ϳ9 ms before the onset of the reduction kinetics. In our experiments, the time course of heme b reduction is sigmoidal, with a lag of only ϳ2 ms. We do not know the origin of this discrepancy.…”
Section: Functional Study Of Pufxsupporting
confidence: 90%
“…Moreover, this barrier exerts a significant but moderate effect, slowing the turnover rate by slightly Ͼ2-fold. This is far from the dramatic blocking suggested by previous reports (17,18), but it makes the photosynthetic competence of other bacteria with a native closed LH1 ring easier to understand.…”
Section: Functional Study Of Pufxcontrasting
confidence: 65%
See 2 more Smart Citations
“…It has been suggested that a protein found in both Rhodobacter sphaeroides and Rhodobacter capsulatus called PufX may provide an answer to this question (10). PufX appears to be a member of the LH1 ring, replacing one of the ␣␤ dimers.…”
mentioning
confidence: 99%